2022
DOI: 10.1212/wnl.0000000000200815
|View full text |Cite
|
Sign up to set email alerts
|

Multivariable Prediction Model for Futile Recanalization Therapies in Patients With Acute Ischemic Stroke

Abstract: Background and Objectives:Very poor outcome despite intravenous thrombolysis (IVT) and mechanical thrombectomy (MT) occurs in about 1 of 4 patients with ischemic stroke and is associated with a high logistic and economic burden. We aimed to develop and validate a multivariable prognostic model to identify futile recanalization therapies (FRT) in patients undergoing those therapies.Materials and Methods:Patients from a prospectively collected observational registry of a single academic stroke center treated wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Several predictors of futile recanalization after MT have been identified [11–18]. However, to the best of our knowledge, the present study is the first investigating the predictors of early clinical and long‐term functional outcomes in the optimal setting for MT.…”
Section: Discussionmentioning
confidence: 93%
“…Several predictors of futile recanalization after MT have been identified [11–18]. However, to the best of our knowledge, the present study is the first investigating the predictors of early clinical and long‐term functional outcomes in the optimal setting for MT.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that futile recanalization was less often with intravenous thrombolysis (11%) than for mechanical thrombectomy (34%). with a total percentage of 24% 21 . Thus, the fact that the patients included in the sample I were majority treated with intravenous rtPA could support the reduced percentage observed.…”
Section: Discussionmentioning
confidence: 72%
“…While the mRS is a validated measure to assess poststroke neurological and functional outcomes, 14 whether it is an appropriate tool to quantify non-neurological disability prior to stroke onset is unclear. Past studies have demonstrated that prestroke mRS is a negative prognostic factor for post-EVT outcomes, [15][16][17] however, no study to date has investigated whether these associations apply to both neurological and non-neurological causes of higher prestroke mRS. There is currently little guidance on how to assess non-neurological disability during acute triage, and using prestroke mRS to quantify disability from osteoarthritis and other musculoskeletal diseases has not been validated.…”
Section: Discussionmentioning
confidence: 99%
“…9 Thrombectomy procedure was identified by procedure codes. Stroke severity was identified using International Classification of Diseases, Tenth Revision (ICD-10) codes for National Institutes of Health Stroke Scale (NIHSS)‚ and categorized into the following categories: mild (NIHSS score 0-4), moderate (NIHSS score [5][6][7][8][9][10][11][12][13][14][15], moderate to severe (16)(17)(18)(19)(20), severe (21 or higher), and unknown. The Elixhauser comorbidity index 10,11 was used to identify stroke risk factors and comorbidities, with slight modifications: (1) Atrial fibrillation and atrial flutter were excluded from the arrhythmia category and listed as a stroke risk factor;…”
Section: Icd-10 Codes Used For Identifying Patients and Variables Of ...mentioning
confidence: 99%